Kondobuleng Folk Theater : Representation of Socio-cultural Identity of Bugis-Makassar Coastal Communities - Ramli, Asia; Suminto, Suminto (Universitas Negeri Semarang, 2018)
For the Bajo ethnic group in Teluk Bone, the folk theater named Kondobuleng is no longer known in its place of origin. However, this theater is found in Pangkajene and the Islands and is known as a dance. This theater is even well known as a folk theater performance in Paropo Village, Panakung Subdistrict, and Makassar City, because it is often performed by Sanggar Seni I Lolo Gading at various events and festivals. This study aims to describe and analyze the folk theater focusing on the representation of socio-cultural identity in the coastal communities of Bugis-Makassar in the performance of the folk theater Kondobuleng. Related to the focus of the study, the research background is Paropo Village of the Panakukang District, Makassar. This research used cultural approach with a qualitative analysis method. The results of the research show that the socio-cultural identity in Bugis-Makassar coastal society is represented in the Kondobuleng folk theater performed by Sanggar Seni I Lolo Gading Paropo through a system of sign language, scene, dialogue, character, costume, property, music, and song.